The status of elephant on the Zambian bank of the Middle Zambezi Valley - Chanda, Glory; Tembo, Ackim (Pachyderm, 1993)
The elephant population in the middle Zambezi has been one of the most heavily affected by hunting in southern Central Africa. Since the 15th Century when the Portuguese invaded the area, elephants have never recovered from legal and illegal hunting. In 1991 a survey covering 1,270 sq kms revealed a total of 359, almost half of the number which existed in 1970. Results revealed a high illegal off take and inadequate policy by wildlife authorities in the area.